Human dental follicle mesenchymal stem cells alleviate T cell response in inflamed tissue of Crohn's patients - AKKOÇ, TUNÇ (AVES, 2020)
Background/Aims: Crohn's disease (CD) is a chronic inflammatory condition characterized by various abnormalities that lead to overly aggressive T cell responses. Our in vitro experiments aimed to investigate the potential use of Dental Follicle Mesenchymal Stem Cells (DF-MSCs) to suppress the exaggerated immune response in inflamed and noninflamed tissue of CD. Materials and Methods: Dental follicle tissues were obtained from extracted third molar teeth of three healthy volunteers who had no abscess or inflammatory diseases. In total, 11 patients were included in the experiment who had been diagnosed with CD and did not receive steroid maintenance therapy for more than one month. Mononuclear cells were isolated from inflamed and noninflamed tissues of CD. Isolated cells were stimulated with anti-CD3/anti-CD28 monoclonal antibodies in the presence and absence of DF-MSCs and analyzed for lymphocytes proliferation capacity and viability, T lymphocyte subsets, CD4+IL22BP and CD4+CD25+Foxp3+ regulatory T cell (Treg) frequencies and cytokine levels. Results: A significant downregulation of lymphocyte proliferation and CD4+IL22BP T cell ratio were found in inflamed cultures with DF-MSCs (p<0.005). Additionally, the frequency of Tregs increased with DF-MSCs (p<0.05). Proinflammatory cytokine levels (Tumor Necrosis Factor (TNF)-a and IL-6) were decreased (p<0.05), and IL-10 levels were increased (p<0.05) in the supernatant of inflamed cultures. Conclusion: DF-MSCs reduced the inflammatory immune response, induced Tregs, and downregulated CD4+IL22BP T cell ratio in inflamed samples of CD patients, which may be exploited for significant therapeutic use.
Keywords: Mesenchymal stem cells; apoptosis; inflammatory bowel disease; immunomodulation; inflammation; INFLAMMATORY-BOWEL-DISEASE; SUBSETS; THERAPY; INTERLEUKIN-22; COLITIS; CD4(+)